Desain Pembelajaran untuk Menciptakan Wellbeing Class di TK Pangudi Luhur Vincentius - Widoningrum, Wulandari Kusuma; Rahmawati, Dini; Handayani, Arri (Universitas Tanjungpura, 2025)
This research aims to analyze how learning design at Pangudi Luhur Vincentius Kindergarten can support the welfare of early childhood. Early childhood well-being includes physical, emotional, social and psychological aspects that are interrelated and influence their development. In this context, learning design is not only oriented towards academic achievement, but also towards developing children's character and social-emotional abilities. This research uses a qualitative approach by collecting data through observation, interviews and questionnaires involving teachers at Pangudi Luhur Vincentius Kindergarten. The research results show that the learning design implemented at this school has paid attention to children's welfare through the integration of social, emotional and physical activities in the learning process. In addition, this research provides recommendations regarding the importance of increasing social interaction and managing emotions in learning design to support the well-being of early childhood.Keywords: early childhood welfare, learning design, social emotional development, Pangudi Luhur Vincentius Kindergarten.